2009
DOI: 10.1007/s00198-009-0884-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported frailty is associated with low calcaneal bone mineral density in a multiracial population of community-dwelling elderly

Abstract: Self-reported frailty is associated with low calcaneal BMD and can be used to identify subjects with a greater risk of osteoporosis than expected from traditional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
(36 reference statements)
1
12
0
2
Order By: Relevance
“…Another study compared three self‐report screening instruments . The studies that reported the highest prevalence used self‐report questionnaires …”
Section: Resultsmentioning
confidence: 99%
“…Another study compared three self‐report screening instruments . The studies that reported the highest prevalence used self‐report questionnaires …”
Section: Resultsmentioning
confidence: 99%
“…Although the relationship between frailty and osteoporosis is not clear, and they may be merely distinct age-related phenomena, some studies showed possible associations [10][11][12]. Fried et al defined frailty as having three or more of the five criteria: unintentional weight loss, self-reported exhaustion, weakness, slow walking speed, and low physical activity in the Cardiovascular Health Study (CHS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Frailty has also been linked in prospective studies with an increased risk of future fractures, though whether this is related to the increased susceptibility to falls or whether there is in addition an associated reduction in bone strength remains uncertain [ 3 ]. Previous studies have investigated the relationship between frailty and bone mineral density (BMD) [ 1 , 4 11 ], however, the results have been somewhat discrepant. Some, though not all, suggest an association between frailty and markers of bone strength, including calcaneal BMD [ 4 ] and femoral neck or lumbar spine BMD [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%